Implementasi Pendidikan Inklusif pada Siswa Berkebutuhan Khusus - Maryam, Maryam; Nasrullah, Amin; Aliyah, Siti Rabiatul (Journal of Instructional and Development Researches, 2024)
This study explores the implementation of inclusive education at MTs Darul Ihsan Anggana, with a specific focus on the school's readiness, curriculum adjustments, and the challenges faced in integrating students with special needs into a regular learning environment. Using a qualitative approach with a phenomenological method, the research involved in-depth interviews, participatory observation, and document analysis to gather comprehensive data on the experiences of students with special needs, teachers, and parents. The results indicate that the school has demonstrated a strong commitment to implementing inclusive education by providing teacher training and adapting the curriculum to accommodate diverse learning needs. However, significant challenges persist, including limited resources, inadequate parental support, and social stigma towards students with special needs. These findings underscore the need for ongoing support from the government and stronger collaboration among schools, teachers, and parents to improve the effectiveness of inclusive education in Indonesia. While inclusive education has shown positive impacts in enhancing the social skills and self-confidence of students with special needs, further curriculum adjustments, increased teacher training, and greater community support are essential to fully optimize learning outcomes and create a more inclusive educational environment for all students.